2015
DOI: 10.1177/2055116915623561
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonosis in cats with diarrhoea in Hong Kong, China, between 2009 and 2014

Abstract: Case series summaryInfection of the domestic cat by Tritrichomonas blagburni, previously referred to as T foetus, may lead to a disease called feline trichomonosis, which manifests clinically as large bowel diarrhoea. The disease has a wide geographical distribution, including numerous countries in Europe, North America and Australia/Oceania. Nevertheless, it has occasionally been reported in Asia, South Korea and Japan. A retrospective study was carried out to include all domestic cats with diarrhoea, present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…The prevalence of the parasite in Japanese cats was 8.8% (8) among animals in three different hospitals. Studies carried out in China between 2009 and 2014 showed that T. foetus was more often found in young purebred cats (86%) (28).…”
Section: Feline Tritrichomonosismentioning
confidence: 99%
“…The prevalence of the parasite in Japanese cats was 8.8% (8) among animals in three different hospitals. Studies carried out in China between 2009 and 2014 showed that T. foetus was more often found in young purebred cats (86%) (28).…”
Section: Feline Tritrichomonosismentioning
confidence: 99%
“…Male cats are reported to be more likely to have positive PCR test results for T. foetus . By dividing these groupings further into sex and neuter status, and in consideration of other factors including age and breed, we did not observe a significant association between sex and probability of a positive PCR test result for T. foetus infection.…”
Section: Discussionmentioning
confidence: 59%
“…Co-infection with other intestinal parasites, such as Giardia species (Gookin et al 2004, Bissett et al 2008, Stockdale et al 2009, Kingsbury et al 2010, Köster et al 2015, Cryptosporidim species (Stockdale et al 2009), coccidia like Isospora species (Stockdale et al 2009), Sarcocystes species (Kingsbury et al 2010), and Toxoplasma gondii (Miró et al 2011), has been already reported. The most common co-infections are Giardia species and coccidia (Tolbert & Gookin, 2009).…”
Section: Discussionmentioning
confidence: 99%